Implementation of Differentiated Learning Assisted by Digital Flipbook to Improve Critical Thinking Ability of Elementary Students in Pancasila Education - Fridayanti, Lucky Angel; Tirtoni, Feri (Universitas Cokroaminoto Palopo, 2025)
This study is motivated by the importance of developing students' critical thinking skills. Critical thinking becomes the mother of competence, because critical thinking is one of the main objectives in the 21st century. This study aims to determine and evaluate the results of the implementation of differentiated learning assisted digital flipbooks on the critical thinking skills of fourth grade students of SDN Simomulyo IV in the subject of Pancasila Education. The method used is a quantitative approach with a Quasi Experiment Non Equivalent Control Group Design research design involving 2 classes and a total of 57 students selected by purposive sampling technique. Class IV-A as the experimental class while class IV-C as the control class. The instruments for this study include critical thinking tests, observations and interviews. Data were analyzed using normality test, homogeneity test and hypothesis test (t-test for independent samples). The results of the analysis showed that the pre-test scores of the experimental and control classes were normally distributed. Homogeneity test proved homogeneous variance. Independent Sample T-Test hypothesis test shows a significant effect on post-test results in both classes. This is evidenced in the t-test results that the sig (2-tailed) value is 0.03 <0.05. The average value of the experimental class post-test of 80.17 is higher than the control class with an average value of 76.50. The discussion in this study emphasizes that the implementation of differentiated learning aided by digital flipbooks is quite effective in improving students' critical thinking skills. Based on the results of the study, it shows that the implementation of differentiated learning is a type of approach that is quite effective in improving the critical thinking skills of elementary school students. This approach can be an innovative learning in accommodating student diversity.